PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SD NEGERI 018 PULAU KIJANG - Asnimar Asnimar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The background of this study is the learning outcomes of social studies students of class VI SDN 018 Pulau Kijang. This isbecause the teacher's system teaches in the classroom that is still using the lecture and reading method, so that students feelbored in learning. This research is a classroom action research conducted at SDN 018 Pulau Kijang. The results of this studyshow that teacher activity in the first cycle of the 1st meeting with a percentage of 56%, the second meeting with apercentage of 73.5%, in the second cycle at the third meeting percentage of 86%, and at the 4th meeting percentage obtained95%. Student observation data in the first cycle of the 1st meeting amounted to 52.5%, the second meeting was 63%, in thesecond cycle the third meeting was 85%, and the fourth meeting was a percentage of 96%. In addition, the results of thestudy in the initial data obtained an average of 65, on the daily test I obtained a class average of 77, and the daily test IIobtained an average of 89.